The flesh ethanolic extract of Hylocereus polyrhizus exerts anti-inflammatory effects and prevents murine colitis. Issue 6 (December 2016) - Macias-Ceja, Dulce C.; Cosín-Roger, Jesus; Ortiz-Masiá, Dolores; Salvador, Pedro; Hernández, Carlos; Calatayud, Sara; Esplugues, Juan V.; Barrachina, Maria D.
Summary: Background & aims: IBD is a chronic disorder of the gastrointestinal tract characterized by mucosal inflammation and epithelial damage. Biologic therapy has significantly improved the course of the disease but there are still a high percentage of patients that do not respond to current therapies. We aim to determine the effects of the flesh ethanolic extract of Hylocereus polyrhizus (EH) in a mice model of colitis induced by TNBS. Methods: Balb/c mice received TNBS (175 mg/kg, 100 μl, i.r.) and six and thirty hours later were administered with EH (1 g/kg, i.p.). Mice were weighted daily and after sacrificing (2 and 4 days after TNBS) we analyzed mucosal histology, myeloperoxidase activity (MPO), the expression of pro-inflammatory molecules (qPCR) and NF-κB and Iκβ-α protein levels. The chemical characterization of the EH was determined by LC–MS/MS. Results: The administration of EH to TNBS-treated mice prevented (P < 0.05) the loss of body weight and significantly reduced in the colon: a) histological damage score, b) MPO enzymatic activity c) the expression of pro-inflammatory molecules and d) Iκβ-α degradation and nuclear NF-κβ protein levels. The LC–MS analysis detected metabolites such as polyphenols and fatty acids. Conclusion: Systemic administration of the ethanolic extract of H. polyrhizus exerts an anti-inflammatory effect and prevents murine colitis induced by TNBS.